2020
DOI: 10.3390/dj8010004
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Fixed Orthodontic Appliance and Clear Aligners on the Periodontal Health: A Prospective Clinical Study

Abstract: This study aimed to evaluate the periodontal health of orthodontic patients with supportive periodontal therapy in a 3 month follow-up. The sample comprised 20 patients (mean age 20.6 ± 8.1 years) in treatment with multibracket fixed appliances (fixed group—FG) and 20 patients (mean age 34.7 ± 12.5 years) in treatment with clear aligners (clear aligners group—CAG). At baseline (T0) and after 3 months (T1), probing depth (PD), plaque index (PI), bleeding on probing (BOP), and gingival recession (REC) were measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
1
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(70 citation statements)
references
References 33 publications
(34 reference statements)
0
43
1
6
Order By: Relevance
“…According to our findings, it could be speculated that different orthodontic appliances could exert different influences on the composition and quantity of the subgingival microbiota due, presumably, to their different encumbrance and removability. That being said, these differences do not necessarily have a clinical implication on gingival health, which instead seems be guaranteed by good motivation for performing optimal home hygiene procedures 19 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to our findings, it could be speculated that different orthodontic appliances could exert different influences on the composition and quantity of the subgingival microbiota due, presumably, to their different encumbrance and removability. That being said, these differences do not necessarily have a clinical implication on gingival health, which instead seems be guaranteed by good motivation for performing optimal home hygiene procedures 19 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, several prospective studies have indicated that patients treated with CAs have better periodontal health indices than subjects treated with FAs, 16,17 but no significant differences in the oral microbiome composition 10,18 . Of note, these differences in periodontal health disappear when continuous reinforcement of home hygiene procedures is provided by a dental hygienist 19 …”
Section: Introductionmentioning
confidence: 99%
“…However, these choices would have been more time-consuming and would have caused aesthetic discomfort due to the presence of the appliance. Additionally, during both vestibular [60] and lingual [61] orthodontic therapies, dental hygiene procedures are more complex and oral microbiology could change.…”
Section: Discussionmentioning
confidence: 99%
“…Tyrimo metu buvo atrinkti 6 viso teksto moksliniai straipsniai, atitikę atrankos kriterijus [5,13,[17][18][19][20]. Mokslinių straipsnių analizės rezultatai pateikti 2 lentelėje.…”
Section: Tyrimo Rezultataiunclassified